2013
DOI: 10.1021/jp310012v
|View full text |Cite
|
Sign up to set email alerts
|

Modulated Intermolecular Interactions in Ferrocenylalkanethiolate Self-Assembled Monolayers on Gold

Abstract: Redox-labeled self-assembled monolayers (SAMs) on gold are excellent model systems for the study of long-range electron transfer processes at electrolyte–electrode interfaces, particularly the distance and reorganization energy dependences. In this work, we have shown that the intermolecular interaction among redox centers is in fact a crucial factor in the overall, nonideal electrochemical response of ferrocenylalkanethiolate SAMs on gold. In both single-component and high-ratio binary monolayers of 11-ferroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
96
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(119 citation statements)
references
References 38 publications
14
96
0
1
Order By: Relevance
“…We have recently investigated the redox properties of single-component 11-ferrocenyl-1-undecanethiolate (FcC11S-Au) and of binary SAMs when mixed with 1-undecanethiol (C11SH), in particular when the surface density of ferrocenylundecanethiolates (G Fc ) increases or a small amount of less polar solvent was added to the aqueous electrolyte [31]. Herein we focus on a comparison of the redox properties of these monolayers when examined in aqueous solution and in the organic phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently investigated the redox properties of single-component 11-ferrocenyl-1-undecanethiolate (FcC11S-Au) and of binary SAMs when mixed with 1-undecanethiol (C11SH), in particular when the surface density of ferrocenylundecanethiolates (G Fc ) increases or a small amount of less polar solvent was added to the aqueous electrolyte [31]. Herein we focus on a comparison of the redox properties of these monolayers when examined in aqueous solution and in the organic phase.…”
Section: Resultsmentioning
confidence: 99%
“…2 obtained in the aqueous phase (-0.88 and -0.12). We previously attributed the two pairs of redox peaks to two structural domains of different packing densities [31]; the "merging" of these peaks into a single pair indicates that the monolayer becomes fairly uniform in the organic phase. We believe that the introduction of organic electrolyte (NB thin film) affects the monolayer structure, leading to the "homogenized" redox behavior of FcC11S-/C11S-Au SAMs.…”
Section: Tablementioning
confidence: 99%
“…An earlier investigation focused on the effects of the micellization of NaC n SO 4 in aqueous solution and surfactant chain length (6,8,10, and 12 carbons) on the redox electrochemistry of FcC 12 SAu SAMs. 6 We demonstrated that alkyl sulfate anions pair with SAM-bound ferroceniums and E°′ shifts to lower potential with increasing chain length.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The electrochemical data is given in Table I The two pairs of redox peaks are attributable to electrochemically distinct ferrocene populations of differing intermolecular interactions caused by the heterogeneity in the surface density and molecular ordering of the ferrocenylalkanethiolates across the SAM. (10,25) Electrostatic repulsion between the ferrocenium cations and steric constraints/crowding render the oxidation of ferrocenes found inside close-packed domains less favorable (higher anodic potential) than those located at domain boundaries and monolayer defect sites (lower potential). (2,5,7,10,26) The first pair of peaks is centered at 305 mV and the second pair is at 417 mV.…”
Section: Resultsmentioning
confidence: 99%
“…(22) The total charge associated with ferrocene oxidation gives an electrogenerated ferrocenium surface concentration of 4.6 (± 0.3) × 10 -10 mol cm -2 , which is close to the theoretical maximum surface coverage of ferrocene of 4.5 × 10 -10 mol cm -2 . (4) The mathematical deconvolution of the anodic scan using Gaussian-Lorentzian fitting (10,25,27) yields the full width at half-maximum ( E fwhm ) of each anodic peak (Table 1). E fwhm of the peak II ferrocene population is significantly larger than 90.6 mV, reflecting the predominance of repulsive interactions between the ferroceniums, consistent with the assignment of the higher potential redox peaks to closely-packed ferrocenes.…”
Section: Resultsmentioning
confidence: 99%